WikiLOR : a collaborative approach to improve learning object metadata - Chiaradía, Marcelo
The quality of metadata in learning object repositories is frequently low; metadata records are incomplete, inaccurate, and out of date. This paper introduces a collaborative, metadata editing approach to improve metadata quality and completion by the community’s effort. WikiLOR is a wiki that acts as both: a learning object repository and a collaborative metadata editor. WikiLOR proposes a wiki-way for editing both a learning object’s content and its metadata. WikiLOR encourages collaborative editing, promotes discussion, helps in conflict resolution and supports version management. The paper additionally documents an experiment that reveals the qualities of WikiLOR and compares it to other benchmark applications.